1998
DOI: 10.1038/sj.bjp.0701869
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhibitors of the activity of cyclo‐oxygenase‐2 on the hypotension and multiple organ dysfunction caused by endotoxin: A comparison with dexamethasone

Abstract: 1 Endotoxaemia is associated with the expression of the inducible isoform of cyclo-oxygenase, cyclooxygenase-2 (COX-2), and an overproduction of arachidonic acid (AA) metabolites. The role of the AA metabolites generated by COX-2 in the circulatory failure and multiple organ dysfunction caused by endotoxin is unclear. Dexamethasone prevents the expression of COX-2 and exerts bene®cial e ects in animal models of shock. 2 Here we compare the e ects of two inhibitors of COX-2 activity, namely NS-398 (5 mg kg 71 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 37 publications
2
34
0
1
Order By: Relevance
“…2 ). The ED 50 for PEinduced contraction in ring segments of LPS-treated rats was 459 ± 83 nM compared with 57 ± 6 nM for vehicle-treated controls ( P < 0.001). 4F administration in the absence of LPS treatment did not alter the response to PE (ED 50 = 69 ± 8 nM).…”
Section: Chromatographic Colocalization Of 4f and Lps In Hdlmentioning
confidence: 99%
“…2 ). The ED 50 for PEinduced contraction in ring segments of LPS-treated rats was 459 ± 83 nM compared with 57 ± 6 nM for vehicle-treated controls ( P < 0.001). 4F administration in the absence of LPS treatment did not alter the response to PE (ED 50 = 69 ± 8 nM).…”
Section: Chromatographic Colocalization Of 4f and Lps In Hdlmentioning
confidence: 99%
“…The present results are also the first demonstration that both COX isoforms are required for the hypotensive response to LPS to develop. With a single exception (33), all previous studies found that COX-2 is not required for the development of LPS hypotension (47,87), and one study (87) found that COX-1 is also uninvolved in this response. However, it should be considered that all previous studies were performed in anesthetized rats receiving fluid resuscitation.…”
Section: Effects Of Cox-1 and Cox-2 Inhibitors On Lps-induced Responsesmentioning
confidence: 99%
“…However, it should be considered that all previous studies were performed in anesthetized rats receiving fluid resuscitation. Under these conditions, rats respond to high doses of LPS with a slowly developing, progressive fall in blood pressure (47,87). The present study was conducted in unanesthetized rats not receiving fluid resuscitation, conditions under which rats respond to high doses of LPS with a rapid drop in blood pressure that corresponds in time to the first phase of the hypothermic response (70).…”
Section: Effects Of Cox-1 and Cox-2 Inhibitors On Lps-induced Responsesmentioning
confidence: 99%
“…Moreover, COX-2 inhibition has been shown to ameliorate liver I/R injury (21)(22)(23) and to reduced liver injury and hepatic microcirculatory dysfunction in response to LPS (24). In contrast, inhibition of COX-2 failed to attenuate hepatocellular injury in rats with endotoxemia (25), and COX-2-deficient mice showed more susceptibility to Con A-induced hepatitis (26). Furthermore, it has been reported that COX-2 inhibition blocked the effect of arachidonic acid, but not of ethanol, on the induction of collagen type I gene expression by stellate cells (27).…”
mentioning
confidence: 99%